A Communication-Based Approach to Adoptive Identity: Theoretical and Empirical Support. (July 2017) - Colaner, Colleen Warner; Soliz, Jordan
The current study uses structural equation modeling to examine adoptive parent communication as it relates to adoptee adjustment directly and indirectly through adoptive identity. Using retrospective accounts of 179 adult adoptees, findings indicate that both adoption- (adoption communication openness) and non-adoption-related (parental confirmation and affectionate communication) parental communication are related to adoptive identity work and positive affect about adoption and birth parents. Preoccupation mediates the relationship between parental communication and adoptee adjustment. The current study integrates research and theorizing from identity, adoption, and communication literatures to develop a communication-centered conceptual model of adoptive identity development to inform future adoption research and practice.